Using audio to support animated route information in a hospital touch-screen kiosk. - Wright, P; Soroka, A; Belt, S; Pham, D; Dimov, S; Roure, D; Petrie, H (2010)
It can be difficult for both patients and staff to find particular locations within large, modern hospital building complexes. Interactive way-finding information on a touch-screen kiosk might remedy this, but numerous design issues face those developing appropriate interfaces. This paper discusses the decisions underlying a design which provided routes to 16 destinations in the UK's third largest hospital, for both stair users and those wishing to avoid stairs. All routes included an animated map, photographs and text boxes with optional spoken output. Assessment methods included unobtrusive observation of kiosk users, analysis of computer logs, and interviews with reception staff who normally answered way-finding queries. Observation confirmed that people using the touch-screen reached their destinations. The computer logs over 10 weeks showed a stable daily average of 82 people interacting with the kiosk. Most way-finders (72%) retained the voice output but 28% turned it off, suggesting that modality choice is needed in multimedia interfaces for the public. This study highlighted beneficial side-effects of interactive way-finding kiosks, such as enabling patients to access relevant route information before visiting the hospital. This information could be provided via the internet or by including a printout of the relevant route with the appointment letter. © 2009 Elsevier Ltd. All rights reserved.